PROSES KOGNITIF KREATIF MAHASISWA TINGKAT I DALAM BELAJAR KEWARGANEGARAAN MELALUI PEMBELAJARAN KONSTRUKTIF KONTEKSTUAL SECARA VIRTUAL - Dewi, Dinie Anggraeni; Nur’aeni, Nani (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
This study aims to find a description of the creative cognitive process abilities of students in learning citizenship, through virtual contextual constructive learning. The research uses a qualitative approach with classroom action research methods, based on online learning via whatsapp, zoom meeting/google meet and google classroom. The research subjects were first semester students at the Faculty of Teacher Training and Education, Universitas Islam Nusantara who took Citizenship Education courses. The research method used is action research with a practical action research model / classroom action research. The indicators for measuring creative cognitive processes include: the ability to identify, formulate problems and create hypotheses to solve problems, the ability to plan realistic solutions, and the ability to construct knowledge by mapping the content of appropriate concepts in learning outcomes. The results showed that contextual constructive learning through virtual learning could develop the creative cognitive process ability of level 1 students in learning citizenship, with a "good" score (77.3 %). This result is not optimal, if it is associated with the ideal value standard of "very good" (85 - 100%). This is found to be lacking in some grade I students in generating creative ideas, namely: students lack high confidence in the truth of their thoughts, if they do not see the internet, do not spontaneously express rationalization of their thinking abilities, express their thinking ideas only imitate other people's statements, have not been able to explain in detail and coherently on the problem and do not elaborate on the problem solving given, less explore literature sources as a reference for thinking in giving birth to problem solving ideas.